2012
DOI: 10.1097/ta.0b013e31822c1b5b
|View full text |Cite
|
Sign up to set email alerts
|

The PHILOS plate for proximal humeral fractures—Risk factors for complications at one year

Abstract: This study points out several predisposing factors for negative outcome after open reduction and internal fixation with the Proximal Humerus Interlocking System plate (fracture type: 11-A3, fracture dislocations, and smoking). Accounting for these, patient's risk for complications can be evaluated more individually and taken into consideration for the concept of treatment. Altering the surgical technique was associated with a significant reduction in the incidence of secondary screw cutout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 22 publications
3
54
0
6
Order By: Relevance
“…In one recent systematic review the overall rate of complications was 49% including varus malunion, 33% excluding varus malunion, and reoperation rate was 14%. The most common complications included varus malunion 16%, AVN 10%, screw perforation of the humeral head into the joint 8%, subacromial impingement 6%, and infection 4% [26] . Various studies have stressed out the association of high rate of complications and need for reoperation [23,26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…In one recent systematic review the overall rate of complications was 49% including varus malunion, 33% excluding varus malunion, and reoperation rate was 14%. The most common complications included varus malunion 16%, AVN 10%, screw perforation of the humeral head into the joint 8%, subacromial impingement 6%, and infection 4% [26] . Various studies have stressed out the association of high rate of complications and need for reoperation [23,26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…A radiologist (NK) independently analyzed the BMD of the same shoulders on pQCT, using a validated protocol for the proximal humerus [14]. Measurement of the cancellous bone of the humeral head was used as the standard of reference for local BMD, as this area is the most common location of failure after ORIF for proximal humerus fractures [11,24]. Correlations between the deltoid tuberosity index and the Tingart measurement, between the deltoid tuberosity index and the Tingart measurement and BMD of the humeral head, and between the deltoid tuberosity index and Tingart measurement and age were calculated.…”
Section: Measurement Of the Deltoid Tuberosity Indexmentioning
confidence: 99%
“…[6][7][8] However, treatment using locking plates has been shown to be associated with postoperative complications such as avascular necrosis, intra-articular penetration of the locking screws. 11,17,18) Our study also described a subset of patients with postoperative complications such as intraarticular perforation of locking screws and non-union. Despite surgical treatment, we also found that 6 patients (11%) still had a 'poor' Constant score.…”
Section: Discussionmentioning
confidence: 99%
“…In general, avascular necrosis is a relatively commonly occurred complication in treating proximal humeral fractures, however in our study none was seen with this complication. 17,28) This could be because the elapsed time was short and a preferential treatment of humeral head replacement over locking plates in the patients aged over 70 who had a 4-part fracture.…”
Section: Discussionmentioning
confidence: 99%